Student perception toward service quality provided at Universiti Utara Malaysia Parcel Centre (UPC) - Yunus, Nurul Syuhada; Zalazilah, Mohd Hanizan (Universiti Utara Malaysia, 2020)
This study looked into student perception about the service quality provided at University Utara Malaysia Parcel Centre (UPC). Based on the performances, this study will find out the effects of quality service on students’ perceptions. Besides, this study will also identify the relationship between service quality and timeliness with students’ perceptions. A research framework has been developed in this study to investigate the relationship between the independent variable and the dependent variable. The service quality attributes used in this study are based on service quality dimensions introduced by Parasuraman et.al.(1988). One hundred UUM students have been chosen randomly in the School of Technology Management &Logistics (STML) building area for study. For data analysis, this study used “Statistical Package for Social Science’ or SPSS software.